Harnessing deductions to increase tax compliance and formalization - Albrecht Bohne; Jan Sebastian Nimczik (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
We evaluate a tax reform in Ecuador that introduced generous deductions from personal income taxes (PIT), encouraging consumers to request receipts. The reform addresses tax evasion by targeting small self-employed businesses that mainly sell goods or services not subject to VAT but often evade income taxes. Exploiting plausibly exogenous variation in receipt demand due to the distribution of taxpayers across regions and professions, we find significant increases in reported profits among self-employed businesses exposed to the reform. We document spillover effects on the VAT system. Our net-revenue impact analysis suggests that the additional tax payments outweigh the foregone tax revenue.
Keywords: O17; H26; H24; H25; 330; Formalization; Tax Avoidance; VAT; Personal Income Tax